2023
DOI: 10.1093/europace/euac237
|View full text |Cite
|
Sign up to set email alerts
|

Global burden of atrial fibrillation/atrial flutter and its attributable risk factors from 1990 to 2019

Abstract: Aims The aim of this study was to estimate the global burden of atrial fibrillation (AF)/atrial flutter (AFL) and its attributable risk factors from 1990 to 2019. Methods and results The data on AF/AFL were retrieved from the Global Burden of Disease Study (GBD) 2019. Incidence, disability-adjusted life years (DALYs), and deaths were metrics used to measure AF/AFL burden. The population attributable fractions (PAFs) were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…The World Health Organization recommended that daily salt intake should be less than 5 g to reduce the risk of cardiovascular diseases ( 8 ). In the Global Burden of Diseases Study (GBD 2019), high salt diet is one of the major risk factors of AF-related death ( 9 ). Studies in recent years suggested that high salt diet may also be a potentially modifiable risk factor for AF.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization recommended that daily salt intake should be less than 5 g to reduce the risk of cardiovascular diseases ( 8 ). In the Global Burden of Diseases Study (GBD 2019), high salt diet is one of the major risk factors of AF-related death ( 9 ). Studies in recent years suggested that high salt diet may also be a potentially modifiable risk factor for AF.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of information on several key confounders we acknowledge that there may be residual confounding. Smoking and alcohol can increase the risk of AF 37 and also affects thyroid function, 12 but individual‐level information on this was not available. Also, increasing BMI is associated with AF, 38 but was not available.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking and alcohol can increase the risk of AF 37 and also affects thyroid function, 12 but individual-level information on this was not available. Also, increasing BMI is associated with AF, 38 but was not available.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…According to data from the Global Burden of Disease study 2019, AF caused about 300,000 deaths while 59 million patients suffer from AF. [1] The progressive nature of disease progression complicates the assessment and treatment of AF. [2] AF typically begins as paroxysmal AF, characterized by intermittent arrhythmia periods lasting less than 7 days, and tends to progress over time to persistent AF (perAF).…”
Section: Introductionmentioning
confidence: 99%